Prarancangan Pabrik Asam Format Dengan Proses Hidrolisis Metil Format Kapasitas 20.000 Ton/Tahun - Saputra, Angga Listya; , Ir. Haryanto A.R ., M.S; , Rois Fatoni S.T., M.Sc., Ph.D (2017)
Formic acid is commonly use as kougulan on natural rubber, latex preservatives, pH controling on the textile industry, it use in the tanning process on the leather industry, and as an anti-bacterial additives on animal food industry. Pre-draft of Formic Acid Factory with Hydrolysis Process of Methyl Format with capacity for about 20,000 tons / year. The formation of formic acid is a hydrolysis reaction which is conducted by reacting methyl formate with water. The reaction that happen is an endothermic reaction and done in a flow stirred tank reactor (RATB) . This reaction was conducted on the condition of 80°C and a pressure of 3 atm. Raw material for methyl formate that needed at this plant is for about 2,914.719 kg / hour and water as much as 1,276.747 kg / hour. The resulting product is formic acid as 2,216.566 kg / hour as the main product and methanol for about 1,618.065 kg / hour as a byproduct. The steps include the preparation of raw materials of methyl formate and water, formic acid formation in the reactor, and the purification results in the distillation tower. To support the production process, some supporting units are needed like units of utilities that includes procurement and processing water as much as 23,213.69 kg / hour, amounting to 324,415 kW of electricity procurement, procurement of steam as 202.77 kg / hour, the procurement of fuel such as diesel as 354.246 L / hour and provision of compressed air as much as 97,459 m3 / hour. The company that selected is a Limited Liability company (PT), where the number of employees is 118 people with line and staff organizational structure. This factory is will be built in Palembang, South Sumatra in 2018. From economic analysis we get the data like overall expenditure each year is 263.194.047.339,132 rupiah while the total sales of the product is 288.198.045.654,761 rupiah. So the profit before the tax is 26.622.021.276,141 rupiah and the profit after the tax is 18.635.414.893,299 rupiah. The obtained value of Return on Investment (ROI) before the tax amounted to 31.02% and after the tax is for about 21.72%, Pay Out Time (POT) before tax for about 2.4 years after the tax for about 3.1 years, Break Even Point (BEP) 47.66%, and Shutdown Point (SDP) 34.93%. While the Discounted Cash Flow (DCF) is 35.09%. So from economic point of view, the factory is proper to built.